Adrenal Crisis in Children - Soegianto, Sugi Deny Pranoto (Cendana Medical Journal, 2022)
Adrenal Crisis is an acute deterioration of adrenal insufficiency. This condition leads to an emergency condition. The major manifestation of adrenal crisis is hypotension and shock hypovolemic. Unspecified general manifestation would lead to misdiagnosis and suboptimal management of this condition. Comprehensive understanding, early diagnosis, and prompt management are important to prevent morbidity and mortality risks in children with adrenal crisis.